Dinosaurs : an adventure back in time - Ring, Susan; Wilson, Phil (Norwalk, CT : Innovative Kids, 2006)
Provides facts about dinosaurs through a fictional account of a child's journey back to prehistoric times. Includes a jigsaw puzzle.
2.3
K-3
Keywords: Dinosaurs -- Juvenile literature; Dinosaurs; Dinosaurs